Conformity with consumptive behavior in female students who are members of the Salatiga Pinaesaan Association - Mikha Rosalinda Wensen; Berta Esti Ari Prasetya (Cita Konsultindo Research Center, 2023)
This study aims to determine the relationship between Conformity and Consumptive Behavior in female students who are members of the Pinaesaan Salatiga pillar. Consumptive behavior is a buying behavior that is no longer based on rational considerations but rather because of desires that have reached irrational levels anymore. Conformity is an individual's attitude to change his behavior by taking existing norms by accepting ideas or rules that indicate how the individual should behave under certain conditions. This research uses quantitative methods. The subjects in this study are 30 active Satya Wacana Christian University students who are active members of the Pinaesaan Salatiga association. Data were obtained with a rxy value of 0.684 with p = 0.000 (p < 0.05) using the Conformity Scale and the Consumptive Behavior Scale. Thus, it can be concluded that there is a significant positive relationship between Conformity and Consumptive Behavior in female students who are members of the Pinaesaan Salatiga harmony. Thus, the hypothesis proposed is accepted in this study. Thus the higher the Conformity, the higher the Consumptive Behavior, and vice versa the lower the Conformity, the Consumptive Behavior tends to be lower.